Comparing the Use of Transverse Abdominis Plane Block and Splash Block for Postoperative Pain Control in Dogs Undergoing Mastectomy—A Blinded Randomized Prospective Clinical Study - Daniele Corona; Simone K. Ringer; Stefanie Keller; Iris M. Reichler; Regula Bettschart-Wolfensberger; Annette P. N. Kutter (Animals)
To compare the use of postoperative analgesia for mastectomy, 44 dogs were randomly allocated to either the Splash treatment group (group A) or the Transverse Abdominis Plane block treatment group (TAP, group B). Following intramuscular (IM) premedication with pethidine (4 mg kg−1) and acepromazine (0.01 mg kg−1), anesthesia was induced with intravenous (IV) propofol and maintained with isoflurane by an anesthetist (DC) who was unaware of the treatment. In group A, ropivacaine 0.5% (2 mg kg−1) was administered prior to surgical wound closure. In group B, ropivacaine 0.5% (0.8–1 mg kg−1 per point) was administered by ultrasound-guided TAP block with two injection points per treated body side. At the end of the surgery, all dogs received pethidine (4 mg kg−1 IM), meloxicam (0.2 mg kg−1 IV), and acepromazine (0.005 mg kg−1 IV). The animals’ pain was assessed by the anesthetist, who remained unaware of the treatment type used, via the Short Form of the Glasgow Composite Pain Scale. When the pain scores were ≥6, methadone (0.2 mg kg−1 IV) and gabapentin (10 mg kg−1 per oral) were started. When the pain score remained ≥ 6, ketamine (1 mg kg−1 subcutaneously) was administered. The dogs in the TAP block group had lower postoperative pain scores 3–12 h after anesthesia administration was terminated and required significantly less rescue analgesia.